2003
DOI: 10.1002/bse.347
|View full text |Cite
|
Sign up to set email alerts
|

UK environmental policy and the small firm: broadening the focus

Abstract: The poor environmental performance of small and medium-sized enterprises (SMEs) in the UK has been attributed to a wide range of barriers, both internal and external to the firm. However, the debate has seldom considered the interplay of factors beyond 'the firm'. In order for the debate to progress we emphasize the importance of situating the environmental practices of small firms within a context of national policy arrangements. A lack of institutional enfranchisement for SMEs in the UK is a key factor in un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
151
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(156 citation statements)
references
References 22 publications
4
151
1
Order By: Relevance
“…Nevertheless, these works focused on proactive CSR, whereas we studied sustainable practices from a more general perspective, without reference to the intentionality of the approach adopted. However, our results reinforce the conclusions of Brammer et al (2012, p. 423), who argued, ''that the smallest companies perceive significantly fewer benefits of engagement with environmental issues'' (see also Revell and Blackburn 2007;Revell and Rutherfoord 2003;Simpson et al 2004). For most businesses, the reduced operating costs that are linked with the decreased consumption of materials or energy remain very limited.…”
Section: Discussionsupporting
confidence: 88%
“…Nevertheless, these works focused on proactive CSR, whereas we studied sustainable practices from a more general perspective, without reference to the intentionality of the approach adopted. However, our results reinforce the conclusions of Brammer et al (2012, p. 423), who argued, ''that the smallest companies perceive significantly fewer benefits of engagement with environmental issues'' (see also Revell and Blackburn 2007;Revell and Rutherfoord 2003;Simpson et al 2004). For most businesses, the reduced operating costs that are linked with the decreased consumption of materials or energy remain very limited.…”
Section: Discussionsupporting
confidence: 88%
“…More recently, a growing number of studies are examining how networks and alliances influence the engagement of SMEs with environmental and, more broadly, sustainable practices (Lawrence et al, 2006). Support networks, defined by Holt et al (2000, p.34) as a group or groups of "organizations or individuals who are able to offer assistance, advice or other forms of support on a specific problem or issue", may be able to help SMEs traverse barriers that prevent them from adopting sustainable practices (Revell and Rutherfoord, 2003;Simpson et al, 2004). SME owner-managers are more able to influence the wider environment if they collaborate with their peers and other stakeholders (Jenkins, 2009); even competitors may be seen as key stakeholders in this context.…”
Section: Can Smes Impact Environmental Sustainability?mentioning
confidence: 99%
“…Hosking employed the kind of 'twin track' approach Tilley (1999) advocates in order to increase progress towards change whilst weakening any residual resistance. By removing the task of researching the environmental product market from the traders, and undertaking it herself, she traversed some of the barriers to sustainable action (Revell and Rutherfoord, 2003) by providing the shop owners with the names of wholesalers who could supply individually tailored sustainable bags and wrappers (Barkham, 2007). Hosking admits there was a certain amount of effort required to identify such supportive infrastructure, but emphasizes that engaging these diverse 27 organizations in problem solving helped accelerate the diffusion process across the different retail network members (Fell et al, 2009;Hosking, 2007).…”
Section: The Case Of Modbury Devonmentioning
confidence: 99%
“…Most research has concentrated on the barriers and drivers that SMEs face when considering environmental improvements and many empirical studies have found that there is a lack of commitment by many SMEs owner-managers to reduce their negative environmental impact (Revell and Rutherfoord, 2003). This is because many SME owner-managers feel that their impact on the environment is minimal and often see no reason to engage in environmental improvement (Bradford and Fraser, 2008;Drake et al, 2004;Hillary, 2000;Pimenova and van der Vorst, 2004;Revell and Blackburn, 2007;Tilley, 1999).…”
Section: Introductionmentioning
confidence: 99%